Changes in physicochemical properties and structural characteristics of rice starch during extrusion processing: The role of glutelin and different extrusion zones. (December 2022) - Yu, Xiaoshuai; Zhang, Junjie; Wang, Lishuang; Duan, Yumin; Wang, Zhenguo; Xiao, Zhigang; Wang, Peng
Abstract: This study aimed to investigate the effects of glutelin on the structural and physicochemical properties of rice starch in different extrusion zones. The addition of glutelin inhibited the swelling of starch granules in the melting zone while induced the aggregation of starch in the die and extrudate. The results of differential scanning calorimetry and X-ray diffraction confirmed that starch granules were completely gelatinized in the melting zone and the incorporation of glutelin did not change its crystalline pattern. The presence of glutelin slightly increased the short-range order of rice starch while decreasing its iodine-binding capacity and branching degree, whereas no covalent bond was formed between them. In summary, the strong thermo-mechanical and heat-moisture effect of the melting zone promoted the interaction of glutelin and starch, the addition of glutelin had a more obvious effect on the structural properties of starch in this zone, die and extrudate. Highlights: Interactions of starch and glutelin occurred at the melting zone and subsequent zones. No covalent bonding existed between rice starch and glutelin in the extruded complex. The unfolding of glutelin facilitated its binding to starch in the extrusion process. The addition of glutelin altered the thermal property and branching degree of starch.